PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE BERTUKAR PASANGAN DALAM PENINGKATAN KETERAMPILAN BERBICARA BAHASA JERMAN - Nurhidayanti, Nurhidayanti; R, Mantasiah (Universitas Negeri Makassar, 2018)
The purpose of this research was to know the planning, process and outcome of the cooperative learning model of type change of pairs in the speaking skills of the students of class XI MA Galesong Selatan Takalar Regency. This research was the class action research, which consisted of two cycles. The data of this research consists of two types, namely: qualitative data and quantitative data. Qualitative data obtained through observation, whereas the quantitative data obtained through the results of test of speaking skills on the cycle I and cycle II. The data were analyzed by using percentages technique. The results showed that the speaking skills in the first cycle was 60.16%, and in the second cycle reached 73.55%. These results show that the application of the cooperative learning model of type change of pairs improve speaking skills of language GermanyÂ of the student of class XI MA Galesong Selatan Takalar Regency